FLAUT: a mutual sensitivity improvement throughmatched pipe, cavity and thin plate resonance - Abdul Hamid, Syamsul Bahrin (Universiti Teknologi Malaysia, 2021)
Electrostatic transducers promises a great potential in alternative to piezoelectric transducer based on certain advantages such as inherently wide bandwidth and good acoustic matching toair due to the membrane’s low acoustics impedance. There are two basic designs that are popular among electrostatic ultrasonic transducer developer –rigid backplate and micromachine backplate. This paper presents a methodology for improving the sensitivity of an air-coupled ultrasonic transducer by coupling the resonating thin plate, cavity and pipe in a single cell. The proposed device is termed Fluidically Amplified Ultrasonic Transducer (FLAUT) for an air-coupled application. Investigation of the concept of matched thin plate, cavity and pipe, of which the individual geometry is expected to mutually enhance one another. Analytical modelling is utilized to the matched thin plate, cavity and pipe. The analytical modelling identifies therequired geometry for the FLAUT based on the matched operating resonant frequency of 25 kHz. At the end of the paper the prototype of FLAUT is presented where the device was fabricated using additive manufacturing process (3-D printing) which consist of a 50 μm Kapton thin film over a micro stereolithography designed backplate. Here aluminum is coated as the electrode utilizing the thermal evaporation process for both the Kapton film and the backplate. A laser interferometer is utilized to measure FLAUT thin plate displacement which indicates the device is running at 25 kHz fundamental mode. A 30 dB difference is also observed between the deformation velocity of thecavity active region and its surrounding